Overexpression of ß-Ketoacyl Co-A Synthase1 Gene Improves Tolerance of Drought Susceptible Groundnut (Arachis hypogaea L.) Cultivar K-6 by Increased Leaf Epicuticular Wax Accumulation - Lokesh, Uppala; Venkatesh, Boya; Kiranmai, Kurnool; Nareshkumar, Ambekar; Amarnathareddy, Vennapusa; Rao, Gunupuru Lokanadha; Anthony Johnson, Anthony Masilamani; Pandurangaiah, Merum; Sudhakar, Chinta (Frontiers in Plant Science, 2019)
Drought is one of the major environmental constraints affecting the crop productivity worldwide. One of the agricultural challenges today is to develop plants with minimized water utilization and reduced water loss in adverse environmental conditions. Epicuticular waxes play a major role in minimizing water loss. Epicuticular wax covers aerial plant parts and also prevent non-stomatal water loss by forming the outermost barrier from the surfaces. Epicuticular wax content variation was found to be affiliated with the drought tolerance of groundnut cultivars. In the current study, a fatty acid elongase gene, KCS1, which catalyzes a rate-limiting step in the epicuticular wax biosynthesis was isolated from drought tolerant cultivar K-9 and overexpressed in drought-sensitive groundnut cultivar (K6) under the control of a CaMV35S constitutive promoter. Transgenic groundnut plants overexpressing AhKCS1 exhibited normal growth and displaying greenish dark shiny appearance. Environmental scanning electron microscopy (ESEM) revealed the excess of epicuticular wax crystal depositions on the transgenic plant leaves compared to non-transgenic wild type plants. The findings were further supported by Gas Chromatography – Mass Spectroscopic analysis (GC-MS) that revealed enhanced levels of fatty acids, secondary alcohols, primary alcohols, aldehydes, alkanes, and ketones in transgenics compared to wild types. The AhKCS1 overexpressing transgenic groundnut plants exhibited an increase in the cuticular wax content, reduction of water loss, lower membrane damage, decreased MDA content and high proline content compared to that of non-transgenic groundnut plants. Our findings suggest that the AhKCS1 gene plays a major role in combating drought stress by preventing non-stomatal water loss in drought-sensitive groundnut cultivar (K-6).